2011
DOI: 10.1002/wnan.163
|View full text |Cite
|
Sign up to set email alerts
|

Calcium phosphate‐based composite nanoparticles in bioimaging and therapeutic delivery applications

Abstract: Bioimaging and therapeutic delivery applications are areas of biomedicine where nanoparticles have had significant impact, but the use of a nanomaterial in these applications can be limited by its physicochemical properties. Calcium phosphate-based composite nanoparticles are nontoxic and biodegradable, and are therefore considered attractive candidates for bioimaging and therapeutic drug delivery applications. Also, the pH-dependent solubility profiles of calcium phosphate materials make this class of nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 55 publications
1
48
0
1
Order By: Relevance
“…CaP based biomaterials, including α and β-TCP, hydroxyapatite (HA) and calcium sulphate, have been extensively used in orthopaedics as a bone substitute material 26,53,54 . Nanoparticles in a size range of 20-200 nm has been shown to be optimal for intracellular delivery, with bare CaP nanoparticles often undergoing significant levels of agglomeration leading to development of a much larger particle size over time [55][56][57][58] . Thus, currently CaP nanoparticles are largely used with modifications to increase their stability and to control their size in order to improve their capacity to cross the cell membrane 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CaP based biomaterials, including α and β-TCP, hydroxyapatite (HA) and calcium sulphate, have been extensively used in orthopaedics as a bone substitute material 26,53,54 . Nanoparticles in a size range of 20-200 nm has been shown to be optimal for intracellular delivery, with bare CaP nanoparticles often undergoing significant levels of agglomeration leading to development of a much larger particle size over time [55][56][57][58] . Thus, currently CaP nanoparticles are largely used with modifications to increase their stability and to control their size in order to improve their capacity to cross the cell membrane 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles in a size range of 20-200 nm has been shown to be optimal for intracellular delivery, with bare CaP nanoparticles often undergoing significant levels of agglomeration leading to development of a much larger particle size over time [55][56][57][58] . Thus, currently CaP nanoparticles are largely used with modifications to increase their stability and to control their size in order to improve their capacity to cross the cell membrane 57 . Even though use of CaP based nanoparticles as carriers for intracellular delivery of nucleic acids has been explored for 40 years, the inherent osteogenic effect of calcium and phosphate ions released from such particles has not been considered in the majority of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has shown that in vitro studies using ultrasound imaging system has been successfully used to investigate targeted drug/gene delivery and organ imaging in vivo (38,50,51). In this study, ultrasound bio-imaging was used to examine the effects of loading, entrapment, distribution, stability, and morphological architecture of post-embedment procedures in the nanocomposite hydrogel system.…”
Section: Ultrasound Bio-imaging Validation Of the Nanocomposite Hydromentioning
confidence: 99%
“…Calcium phosphate nanoparticles have been recently also used in imaging with organic dyes and lanthanides, and in delivering oligonucleotides and a variety of drugs [100][101][102]. Apatite nanoparticles have been shown to exhibit better fluorescent properties than their amorphous counterparts when doped with lanthanides because of rigid confinement of the lanthanide ions in the crystalline structure of these nanoparticles [103,104].…”
Section: Nanocrystalline Apatites As Bone Substitutes and Drug Delivementioning
confidence: 99%